THE EFFECTIVENESS OF FLASHCARDS ON THE MOTIVATION TO INCREASE ENGLISH VOCABULARY AMONG THE FOURTH ELEMENTARY SCHOOL - Helda Lisa (Journal of Applied Linguistics and Literature)
The primary objective of this study is to find out whether the illustrated flashcards have positive effect on the motivation to increase English vocabulary among elementary school fourth grade students. The problem of this study is why students of elementary school fourth-grade still find difficulties in understanding and comprehending the English material and especially that for vocabulary. The result of the analysis shows that there is a significance difference between the motivation to learn English vocabulary among the elementary school fourth-grade students before the implementation of flashcards and that after the implementation (76,6%), and there is a significant difference between English vocabulary mastery of elementary school fourth-grade students taught by using flashcards and that of those taught without using flashcards(t=7,74).